Occupational exposures and risk of stomach and esophageal cancers: Update of a cohort of female textile workers in Shanghai, China. Issue 3 (21st January 2015) - Gallagher, Lisa G.; Li, Wenjin; Ray, Roberta M.; Romano, Megan E.; Wernli, Karen J.; Gao, Dao L.; Thomas, David B.; Checkoway, Harvey
<x xml:space="preserve">Abstract</x> Background Associations between stomach and esophageal cancer and exposures to dusts, metals, chemicals, and endotoxin in the workplace are not very well understood, particularly in women. Methods We followed 267, 400 female textile workers in Shanghai, China for cancer incidence from 1989 to 2006. Stomach (n = 1374) and esophageal (n = 190) cancer cases were identified and a comparison subcohort (n = 3187) was randomly selected. Cox proportional hazard modeling was used, adjusting for age and smoking. Results Increasing stomach cancer risk was observed with increasing duration of synthetic fiber dust exposure (p = 0.03), although the magnitude of effect was small (20 + years: HR = 1.2, 95% CI 1.1–1.4). Trends with endotoxin exposure were modestly inversed for esophageal cancer and increased for stomach cancer, but with little deviation from a null association. Conclusions Our findings demonstrate that long durations of synthetic fiber dust exposure can increase stomach cancer risk in women, but provide limited support for associations with other textile industry exposures. Am. J. Ind. Med. 58:267–275, 2015. © 2015 Wiley Periodicals, Inc.